Effect of grain structure on the stress corrosion cracking (SCC) behavior of an as-extruded Mg-Zn-Zr alloy. (15th August 2019) - Wang, B.J.; Xu, D.K.; Sun, J.; Han, En-Hou
Highlights: The bi-modal grain structure improves the static corrosion resistance. The formation of coarse grains degrades the SCC resistance. The cracking modes of SCC are determined by the grain structures. Abstract: Through investigating and comparing the microstructure and stress corrosion cracking (SCC) behavior of an as-extruded Mg-6.2Zn-0.8Zr (in wt.%) alloy before and after solid solution treatment (T4), the effects of grain structure on the SCC resistance and cracking modes have been disclosed. Slow strain rate testing (SSRT) results demonstrated that the SCC resistance decreased with the increased fraction of coarse grains. Failure analysis indicated that for the finely grain-structured samples, the cracking mode was dominated by the intergranular cracking. For the "bi-modal" grain-structured samples, the cracking mode was intergranular/transgranular mixed type. For the coarsely grain-structured samples, the cracking mode was transgranular.